Sociodemographic Factors and Frequency of Dental Clinic Visits Associated with Oral Health Literacy in the Early Adolescence - Shariq Ali Khan, Sahrish Jabeen, Fariha Fayyaz, Muhammad Abdullah, Adeel Tuasene, Muhammad Adnan Akram (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study is to evaluate the associations between oral health literacy and selected sociodemographic factors and frequency of dental clinic visits in early adolescents. Methodology: A cross sectional study has been conducted for the duration of six Months from April 2021 to September 2021. Students attending four universities of Lahore were selected as a target population for the study. Two universities were selected from government sector i.e. Forman Christian college (FC) and Punjab university (PU). Two universities were chosen from private sector i.e. Superior University and University of Lahore (UoL) for this purpose. A total of 400 students belonging to different departments participated in the study that were clinically examined and interviewed. The students belonged to the different departments of the under- survey universities. To measure oral health literacy REALD-30 was used as a tool. The validity of the tool is checked by Cronbach’s alpha (0.89). The variables were investigated using validated questionnaires: oral health literary (REALD-30), sociodemographic characteristics and frequency of dental visits. Result: The results summed up that REALD-30 score came out differently for those who visit dental clinics regularly (p-value 0.029) and those who don’t which show that the dentist visits have a significant effect on REALD-30 score. The department factor has a significant effect on REALD-30 score, as the department of students varies, the REALD-30 score differs. The F- statistics and the p-value are calculated and their significance is checked, that F=5.357 and the p-value is (.000<0.05), that strongly support that the department factor has a significant effect on the REALD-30 score. Gender discrimination and age variation did not show any effects on REALD-30 score (p-value 0.1)